Sistem Pakar Dalam Diagnosa Penyakit Tuberkulosis Otak Menggunakan Metode Certainty Factor - Alexius Ulan Bani; Fifto Nugroho (STMIK Budi Darma, 2020)
Brain tuberculosis or brain tuberculosis is a type of disease that is very rarely known by many levels of society, brain tuberculosis is also a type of disease that cannot be considered a mild disease at all but a type of disease that can cause sufferers to live in suffering and more often result in death and tuberculosis brain disease is very rarely known to the sufferer and until now the drugs in the treatment of this disease are also very expensive. Diagnosis needs to be done before this disease becomes inflamed and takes over from the brain function itself so that the community will be more sensitive and better recognize and prevent brain tuberculosis disease from approaching, in this study an application in the diagnosis of brain tuberculosis is carried out using an expert system approach which is used to assist in Diagnosis of tuberculosis brain disease using the certainty factor method, the results of using the certainty factor method based on the criteria and every listed symptom that many patients with brain tuberculosis experience show a fairly high percentage and accuracy as a means of showing the condition of the body experiencing symptoms of brain tuberculosis.